Divine Doppelgängers: YHWH's ancient look-alikes - Cornell, Collin (Eisenbrauns, 2020)
God and the gods : history of religions as an approach and context for biblical theology / Patrick D. Miller, Jr. -- Canaan--Israel--Christianity : the case for a vertical ecumenism / Othmar Keel, trans. by Armin Siedlecki -- More than one god? : three models for construing the relations between YHWH and the other gods / Bob Becking -- Who is like you among the gods? : some observations on configuring YHWH in the Old Testament / J. Andrew Dearman -- Why should the look-alikes be a problem? / Robert Goldenberg -- Theological approaches to the problem of God's ancient look-alikes / Collin Cornell -- Chemosh looks like YHWH but that's okay / Josey B. Snyder -- YHWH and Chemosh : an investigation of look-alike gods using the moral foundations theory / M. Patrick Graham -- YHWH, Chemosh, and the Regula fidei / Brent A. Strawn -- Is there a counterpart in the Hebrew Bible to New Testament antisemitism? / Jon D. Levinson -- Miqreh and YHWH : fate, chance, simultaneity, and providence / Stephen B. Chapman -- 'Can a woman forget her nursing child?' : divine breastfeeding and the God of Israel / Christopher B. Hays -- Bulls and horses, gods and goddesses : the religious iconography of Israel's neighbors / P.M. Michèle Daviau.